Efficiencies of NF and RO membranes on pharmaceutical removal and membrane fouling effects - Katanchalee Phadunghus (2018)
© 2017, Chulalongkorn University 1. All rights reserved. The efficiencies of nanofiltration (NF) and reverse osmosis (RO) membranes in removing carbamazepine (CBZ) and sulfamethoxazole (SMX) were studied. To do this, the NF and RO membranes NF-1 and RO-1 were used, and the isoelectric points of the NF-1 and RO-1 membranes were determined to be at approximate pH of 6.0. The NF-1 membrane’s CBZ rejections at solution pH values of 5.0, 6.0, and 7.0 were in a slight range of 92-93%. Additionally, SMX rejections by the NF-1 membrane at the same three solution pH values were 87%, 91%, and 94%, respectively. Meanwhile, the RO-1 membrane’s CBZ rejections at those solution pH values were also in a narrow range of 92-94%, and its SMX rejections were 94%, 97%, and 98%, respectively. Solution pH was found to have no effect on CBZ rejection but it did affect SMX rejection. Mixed pharmaceuticals showed insignificant change in rejections compared with those of single pharmaceutical. The effect of membrane fouling on SMX removal was observed. It was found that when the membranes were fouled by tannic acid (TA) in the presence and absence of calcium chloride (CaCl2), the membrane’s rejection of SMX was improved.